Redesain Pondok Putri Pesantren Islam Al Mukmin Ngruki Sukoharjo (Dengan Pendekatan Ekologi Arsitektur) - Digna, Ifannisa; , Nur Rahmawati S, ST. MT; , Yayi Arsandrie, ST. MT (2016)
Pondok Pesantren Putri Al-believer of Islam is an Islamic institution, which combines education and teaching systems between traditional pesantren education system with modern education developed at this time. The system used is formal and non-formal. He has previously held research at the school that was later found many problems in terms of architecture, especially regarding the occupancy comfort in the bedroom santriwati resulting openings are not optimal, and the old system of the building is too coincide, then this problem can be solved with the concept of ecological architecture. The objective of this scheme is to get a conceptual basis in planning and designing redesigning boarding school with housing needs and is equipped with the proper education and other supporting facilities with ecological approach to architecture as a way out of the problems that already exist.